Proposed framework for planning software releases using fuzzy rule‐based system. Issue 6 (1st December 2019) - Elsaid, Asmaa H.; Salem, Rashed K.; Abdelkader, Hatem M.
Abstract : Software release planning is one of the complicated areas of software engineering. Planning a software release includes assigning requirements to sequence of releases in the most beneficial way within the limited effort, budget, and time available. The complexity of the software release planning is due to the incompleteness and the uncertainty challenges that characterise the software release planning problem. In order to handle efficiently the incompleteness and uncertainty challenges, the computer intelligent fuzzy logic approach can be utilised. Although several methods have been proposed to handle the incompleteness and uncertainty challenges, they are all based on optimisation methods. The objective of this study is to propose a novel framework to handle the uncertainty and incomplete challenges of the software release planning based on intelligent approaches such as fuzzy rule‐based system rather than optimisation method. Also, some predefined thresholds are determined to support the time flexible horizon challenge of the software release planning process and to increase the flexibility of the proposed framework. For validating the proposed framework, it is applied to plan a new release for updating a faculty website project.